Does Perceiving the Poor as Warm and the Rich as Cold Enhance Perceived Social Justice? The Effects of Activating Compensatory Stereotypes on Justice Perception - Fu, Anguo; Zhang, Zaisheng; He, Wuming; Lin, Zhaohong; Wu, Na; Hou, Guanghui; Yao, Tianzeng (Frontiers in Psychology, 2019)
Compensatory stereotypes are the fundamental components of social perception, and competence and warmth are the two fundamental dimensions of social cognition. Previous studies have concluded that, to maintain belief in justice, the system justification motive leads people to believe that upper- and lower-class groups each have their own unique and mutually offsetting advantages and disadvantages (e.g., the rich have low warmth and the poor have high warmth). The present study introduced the variable of social justice perception (personal and systemic justice perception) and hypothesized that endowing upper-class groups with negative characteristics and lower-class groups with positive characteristics could enhance people’s social justice perception. Participants were presented with vignettes that activated compensatory/non-compensatory stereotypes in four ways (compensatory competence, non-compensatory competence, compensatory warmth, non-compensatory warmth) regarding individuals described as rich and poor. Justice perception toward these individuals was then rated by the participants. The results showed that compensatory stereotypes triggered by system justification motives can affect the social justice perceptions of individuals to a certain extent. That is, perceiving the poor as warm and the rich as cold enhance perceived social justice, whereas perceiving the poor as competent and the rich as incompetent reduces perceived personal justice but does not affect perceived systemic justice. Especially in the context of the Chinese Confucian culture, which emphasizes warmth but ignores competence, the effect of compensatory stereotypes on perceptions of social justice underscores a cultural difference with the West that warmth is superior to competence. Further, compensatory stereotypes may be either beneficial for or detrimental to individuals of low socioeconomic status, and the results also question whether justice perception reflects the true fairness of society.